2020
DOI: 10.18321/ectj928
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Antibacterial Properties of PLA-based Ciprofloxacin Composite Films Deposited by Low-Electron Beam Dispersion

Abstract: Polylactic acid (PLA)-based ciprofloxacin (Cip) antibacterial films with mass ratio PLA:Cip=1:1 were prepared by low-electron beam dispersion (EBD). The molecular structure, chemical composition and morphology of PLA-based ciprofloxacin antibacterial films were investigated by XPS, FTIR, liquid NMR and SEM. The antibacterial activity of composite films was tested against E. coli ATCC 25922 and S. aureus ATCC 12600 using the agar diffusion method on the solid LB agar medium. XPS and FTIR analysis showed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…It confirms that PCL and CIP are integrated and are relatively Eurasian Chemico-Technological Journal 22 (2020) 255-262 tightly and uniformly mechanically mixed together. These results indicate that the CIP powder did not degrade significantly under the activation of low-electron beams, which is attributed to the fact that the tendency of ciprofloxacin evaporation is accessible without strong heating and radiation exposure [11].…”
Section: The Results Of Ftir Spectroscopic Analysismentioning
confidence: 80%
“…As it was shown that the antibacterial activity of CIP was tested against E. coli ATCC 25922 and S. aureus ATCC 12600 using the agar diffusion method on the solid LB agar medium [11]. It had proved that CIP has stronger antibacterial activity against S. aureus than E. coli, so in this article, we choose S. aureus to test.…”
Section: Study On Antibacterial and Sustained Release Propertiesmentioning
confidence: 99%
See 1 more Smart Citation